(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
Kitabiyah and ahl al-Kitab are terms that are often used interchangeably to describe a woman who believes in revealed religion possessing a Divine Book, namely Judaism or Christianity. The Islamic Family Law Act and Enactments recognize a marriage between a Muslim man and a Kitabiyah. In the case of Johan bin Abdul Walked Shaik v Runa Bangoe Olsen, the Syariah court found that the marriage solemnized in Australia between parties to the marriage, namely between a Muslim man and a Christian woman, was valid according to the Shari’ah. This case highlights the interpretation of the term kitabiyah made by the Malaysian Syariah court in a Muslim marriage registered under the Islamic Family Law Enactment in Malaysia. The issue of kitabiyah also applies to a situation where a husband converted to Islam and the wife professes a scriptural religion. Thus, the main concern of this paper is to examine the issue of kitabiyah in marriage, conversion of non-Muslim men to Islam, and the implications relating to rights under family law or the law of inheritance. This paper also seeks to examine practical approaches and challenges, especially concerning interfaith marriages. The study adopts doctrinal analysis by examining existing primary and secondary materials, including statutory provisions as provided by the family law enactments of various states, the opinions of the jurists, case law and other legal and non-legal literatures relating to kitabiyah in Muslim marriages from the Islamic perspective and in the Malaysian context. It is suggested that an intensive interpretation of kitabiyah is needed in Malaysia to ensure that the concept of interfaith marriage is not too loosely interpreted. At the same time, the door of ijtihad of the presiding judge in deciding matters relating thereto should not be closed. Keywords: Pillars of marriage, Muslim men, kitabiyah, conversion to Islam, interfaith marriage, inheritance Full text: PDF